2016
DOI: 10.1016/j.jfma.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Home-based virtual reality balance training and conventional balance training in Parkinson's disease: A randomized controlled trial

Abstract: This study did not find any difference between the effects of the home-based virtual reality balance training and conventional home balance training. The two training options were equally effective in improving balance, walking, and quality of life among community-dwelling patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
256
0
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(280 citation statements)
references
References 29 publications
4
256
0
20
Order By: Relevance
“…116 By contrast a home-based VR intervention for balance and mobility was no different than standard of care home physical therapy in changing the PDQ. 124 The frequency with which participation is used as an outcome in studies of people post-stroke was lower than that reported for people with PD or MS. This may in part be explained because of the progressive nature of MS and PD and the belief that participation may be altered but body structure/function may not.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 88%
See 1 more Smart Citation
“…116 By contrast a home-based VR intervention for balance and mobility was no different than standard of care home physical therapy in changing the PDQ. 124 The frequency with which participation is used as an outcome in studies of people post-stroke was lower than that reported for people with PD or MS. This may in part be explained because of the progressive nature of MS and PD and the belief that participation may be altered but body structure/function may not.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 88%
“…Another study suggested no difference when comparing home-based therapy to home based VR therapy. 124 In a study with dancing (with the K Pop Dance Festival from the Wii) added to the standard of care, participants had reduced symptoms of depression and improved balance. 125 The results of the largest multi-center clinical trial on walking with VR, VTIME, are pending.…”
Section: Outcomes Of Vr and Sg Interventionsmentioning
confidence: 99%
“…While the 100% adherence and 0% dropout rates make a high exercise intensity feasible [8], therapists delivered exercise sessions in a designated hospital facility, conditions often unavailable to PD patients. However, patients could perform agility exercises or cycle on an ergometer at home with remote supervision, reducing costs and staff burdens [26,35]. In this randomized comparative effectiveness trial the assessors were blinded to the patients' group assignment; there could still be a bias in the assessments because there was no assessment of masking maintenance.…”
Section: Limitationsmentioning
confidence: 99%
“…Los logros persistieron al menos un mes post-entrenamiento; sin embargo, no se encontraron diferencias significativas con el grupo de ejercicio convencional a excepción del sistema visual, el cual obtuvo mejores resultados, quizás asociados al flujo masivo óptico generado por el entorno virtual (36,37).…”
Section: Experiencias Terapéuticas En Enfermedad De Parkinsonunclassified